Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

In poor taste: leaf palatability traits are not correlated with aboveground enemy release - Zoe A. Xirocostas; Eve Slavich; Susan E. Everingham; Juha-Pekka Salminen; Louis Booth; Roslyn Gleadow; Jeff Ollerton; Riin Tamme; Begoña Peco; Vincent Lesieur; S. Raghu; Robert R. Junker; et al. (Oecologia, 2026)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Determining contemporary and historical sediment sources in a large drainage basin impacted by cumulative effects: the regulated Nechako River, British Columbia, Canada - David Gateuille; Philip N. Owens; Ellen L. Petticrew; Barry P. Booth; Todd D. French; Stephen J. Déry (Journal of Soils and Sediments, 2019)

Temperature influences habitat preference of coral reef fishes: Will generalists become more specialised in a warming ocean? - Paloma A. Matis; Jennifer M. Donelson; Stephen Bush; Rebecca J. Fox; David J. Booth (Global Change Biology, 2018)
Climate change is expected to pose a significant risk to species that exhibit strong behavioural preferences for specific habitat types, with generalist species assumed to be less vulnerable. In this study, we conducted habitat choice experiments to determine how water temperature influences habitat preference for three common species of coral reef damselfish (Pomacentridae) that differ in their levels of habitat specialisation. The lemon damselfish Pomacentrus moluccensis , a habitat specialist, consistently selected complex coral habitat across all temperature treatments (selected based on local average seasonal temperatures naturally experienced in situ: ambient winter 22°C; ambient summer 28°C; and elevated 31°C). Unexpectedly, the neon damselfish Pomacentrus coelestis and scissortail sergeant Abudefduf sexfasciatus , both of which have more generalist habitat associations, developed strong habitat preferences (for complex coral and boulder habitat, respectively) at the elevated temperature treatment (31°C) compared to no single preferred habitat at 22°C or 28°C. The observed shifts in habitat preference with temperature suggest that we may be currently underestimating the vulnerability of some habitat generalists to climate change and highlight that the ongoing loss of complex live coral through coral bleaching could further exacerbate resource overlap and species competition in ways not currently considered in climate change models.

Extreme precipitation and phosphorus loads from two agricultural watersheds - Stephen R. Carpenter; Eric G. Booth; Christopher J. Kucharik (Limnology and Oceanography, 2018)
Phosphorus runoff from agricultural land is a major cause of eutrophication in lakes and reservoirs. Frequency and intensity of extreme precipitation events are increasing in agricultural regions of the Upper Midwestern U.S., and these increases are projected to continue as climate warms. We quantified the linkage between extreme daily precipitation and extreme daily discharge, phosphorus (P) load, and P concentration for Pheasant Branch and the Yahara River, two tributaries of Lake Mendota, Wisconsin, U.S.A. using the generalized Pareto distribution. Although precipitation extremes have increased since 1940, over the shorter period of stream monitoring (1994–2015 for Pheasant Branch and 1991–2015 for Yahara) there is no significant trend in extreme precipitation. Nonetheless a disproportionate number of extreme precipitation events (for example seven of the 11 largest 24‐h events since 1901) occurred during the period of stream monitoring. Daily precipitation extremes were associated with extremes in daily discharge and P load. P load return levels increased steeply and almost linearly with precipitation on log‐log axes. The trend toward more frequent and intense precipitation extremes will increase P loading and intensify the eutrophication of the lake, unless the excessive P enrichment of the watershed is reversed.

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

Extreme daily loads: role in annual phosphorus input to a north temperate lake - Stephen R. Carpenter; Eric G. Booth; Christopher J. Kucharik; Richard C. Lathrop (Aquatic Sciences, 2015)

Changing forest water yields in response to climate warming: results from long‐term experimental watershed sites across North America - Irena F. Creed; Adam T. Spargo; Julia A. Jones; Jim M. Buttle; Mary B. Adams; Fred D. Beall; Eric G. Booth; John L. Campbell; Dave Clow; Kelly Elder; Mark B. Green; Nancy B. Grimm; et al. (Global Change Biology, 2014)
Climate warming is projected to affect forest water yields but the effects are expected to vary. We investigated how forest type and age affect water yield resilience to climate warming. To answer this question, we examined the variability in historical water yields at long‐term experimental catchments across Canada and the United States over 5‐year cool and warm periods. Using the theoretical framework of the Budyko curve, we calculated the effects of climate warming on the annual partitioning of precipitation ( P ) into evapotranspiration ( ET ) and water yield. Deviation ( d ) was defined as a catchment's change in actual ET divided by P [ AET / P ; evaporative index ( EI )] coincident with a shift from a cool to a warm period – a positive d indicates an upward shift in EI and smaller than expected water yields, and a negative d indicates a downward shift in EI and larger than expected water yields. Elasticity was defined as the ratio of interannual variation in potential ET divided by P ( PET / P ; dryness index) to interannual variation in the EI – high elasticity indicates low d despite large range in drying index (i.e., resilient water yields), low elasticity indicates high d despite small range in drying index (i.e., nonresilient water yields). Although the data needed to fully evaluate ecosystems based on these metrics are limited, we were able to identify some characteristics of response among forest types. Alpine sites showed the greatest sensitivity to climate warming with any warming leading to increased water yields. Conifer forests included catchments with lowest elasticity and stable to larger water yields. Deciduous forests included catchments with intermediate elasticity and stable to smaller water yields. Mixed coniferous/deciduous forests included catchments with highest elasticity and stable water yields. Forest type appeared to influence the resilience of catchment water yields to climate warming, with conifer and deciduous catchments more susceptible to climate warming than the more diverse mixed forest catchments.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Decomposing the mid‐Holocene Tsuga decline in eastern North America - Robert K. Booth; Simon Brewer; Maarten Blaauw; Thomas A. Minckley; Stephen T. Jackson (Ecology, 2012)
The mid‐Holocene decline of Tsuga canadensis (hereafter Tsuga ) populations across eastern North America is widely perceived as a synchronous event, driven by pests/pathogens, rapid climate change, or both. Pattern identification and causal attribution are hampered by low stratigraphic density of pollen‐sampling and radiometric dates at most sites, and by absence of highly resolved, paired pollen and paleoclimate records from single sediment cores, where chronological order of climatic and vegetational changes can be assessed. We present an intensely sampled (contiguous 1‐cm intervals) record of pollen and water table depth (inferred from testate amoebae) from a single core spanning the Tsuga decline at Irwin Smith Bog in Lower Michigan, with high‐precision chronology. We also present an intensively sampled pollen record from Tower Lake in Upper Michigan. Both sites show high‐magnitude fluctuations in Tsuga pollen percentages during the pre‐decline maximum. The terminal decline is dated at both sites ca. 5000 cal yr BP, some 400 years later than estimates from other sites and data compilations. The terminal Tsuga decline was evidently heterochronous across its range. A transient decline ca. 5350 cal yr BP at both sites may correspond to the terminal decline at other sites in eastern North America. At Irwin Smith Bog, the terminal Tsuga decline preceded an abrupt and persistent decline in water table depths by ∼200 years, suggesting the decline was not directly driven by abrupt climate change. The Tsuga decline may best be viewed as comprising at least three phases: a long‐duration pre‐decline maximum with high‐magnitude and high‐frequency fluctuations, followed by a terminal decline at individual sites, followed in turn by two millennia of persistently low Tsuga populations. These phases may not be causally linked, and may represent dynamics taking place at multiple temporal and spatial scales. Further progress toward understanding the phenomenon requires an expanded network of high‐resolution pollen and paleoclimate chronologies.

Multi‐decadal drought and amplified moisture variability drove rapid forest community change in a humid region - Robert K. Booth; Stephen T. Jackson; Valerie A. Sousa; Maura E. Sullivan; Thomas A. Minckley; Michael J. Clifford (Ecology, 2012)
Climate variability, particularly the frequency of extreme events, is likely to increase in the coming decades, with poorly understood consequences for terrestrial ecosystems. Hydroclimatic variations of the Medieval Climate Anomaly (MCA) provide a setting for studying ecological responses to recent climate variability at magnitudes and timescales comparable to expectations of coming centuries. We examined forest response to the MCA in the humid western Great Lakes region of North America, using proxy records of vegetation, fire, and hydroclimate. Multi‐decadal moisture variability during the MCA was associated with a widespread, episodic decline in Fagus grandifolia (beech) populations. Spatial patterns of drought and forest changes were coherent, with beech declining only in areas where proxy‐climate records indicate that severe MCA droughts occurred. The occurrence of widespread, drought‐induced ecological changes in the Great Lakes region indicates that ecosystems in humid regions are vulnerable to rapid changes in drought magnitude and frequency.

The impact of acute strenuous exercise on TLR2, TLR4 and HLA.DR expression on human blood monocytes induced by autologous serum - Stephen Booth; Geraint D. Florida-James; Brian K. McFarlin; Guillaume Spielmann; Daniel P. O’Connor; Richard J. Simpson (European Journal of Applied Physiology, 2010)

Epac activation, altered calcium homeostasis and ventricular arrhythmogenesis in the murine heart - Sandeep S. Hothi; Iman S. Gurung; Jennifer C. Heathcote; Yanmin Zhang; Stephen W. Booth; Jeremy N. Skepper; Andrew A. Grace; Christopher L.-H. Huang (Pflügers Archiv - European Journal of Physiology, 2008)

Soil-mixing effects on inorganic nitrogen production and consumption in forest and shrubland soils - Mary S. Booth; John M. Stark; Stephen C. Hart (Plant and Soil, 2006)

Distribution of mid‐ and late‐stage Jasus edwardsii phyllosomas: Implications for larval recruitment processes - Stephen M. Chiswell; John D. Booth (New Zealand Journal of Marine and Freshwater Research, 2005)
The relative distributions of mid‐ and late‐stage phyllosomas, and pueruli, of Jasus edwardsii from five research cruises off the east coast of the North Island of New Zealand were analysed. A statistical approach was taken, using a bootstrapping with replacement method to test whether the observed mid‐ and late‐stage phyllosomas could have come from the same distribution. Differences in distribution between mid‐ and late‐stage phyllosomas were very close to significant at 95% confidence for two cruises, significant at 85% confidence for one cruise, and two cruises showed a non‐significant result. When all cruise data were combined into one analysis, the differences between mid‐ and late‐stage phyllosomas were significant with 85% confidence. On average, late‐stage phyllosomas were found 49 km further inshore than mid‐stage phyllosomas. One station during one cruise and one transect during another showed such high abundances that they affected the analyses. When these outlier data were excluded, the differences in mid‐and late‐stage distributions become significant with 99% confidence. One explanation for observed distribution differences is that the late‐stage phyllosomas swim shoreward—as the pueruli are believed to do. This implies an ability to navigate in both these early life forms. If the late‐stage larvae are indeed swimming horizontally, it is likely that this is most effectively accomplished by final‐stage phyllosomas, which have well developed pleopods, similar to those in the puerulus stage.

Vertical distribution and diurnal migration patterns of Jasus edwardsii phyllosomas off the east coast of the North Island, New Zealand - Russell W. Bradford; Barry D. Bruce; Stephen M. Chiswell; John D. Booth; Andrew Jeffs; Simon Wotherspoon (New Zealand Journal of Marine and Freshwater Research, 2005)
The rock lobster Jasus edwardsii forms the basis of important fisheries in south‐eastern Australia and New Zealand. Their long pelagic larval phyllosoma phase (12–24 months) raises many questions as to how the larvae are retained and/or recruited into local populations. Recent attempts to model the dispersal of J. edwardsii phyllosoma have had mixed success at reconstructing settlement patterns. However, these models have either ignored vertical distribution or have used that of the western rock lobster, Panulirus cygnus. We report on the vertical distribution and migration of J. edwardsii phyllosomas, collected in March/April 2003 from the Wairarapa Eddy off the east coast of the North Island, New Zealand, and provide a model to describe their vertical distribution. J. edwardsii phyllosoma were primarily recorded within the upper 100 m over similar depth ranges to those reported for other palinurid and scyllarid species. Well‐defined changes in diel vertical distribution were restricted to late‐stage larvae. Mid‐stage phyllosomas were concentrated in the upper 20 m both day and night. Late‐stage phyllosomas were concentrated in the upper 20 m during the night, but they were absent from the upper 20 m during the day and distributed primarily between 20 and 100 m. Future modelling will benefit from using larval distribution and behaviour patterns specific to J. edwardsii.

Determination of genotoxic polycyclic aromatic hydrocarbons in a sediment from the Black River (Ohio) - W. Raymond West; Philip A. Smith; Gary M. Booth; Stephen A. Wise; Milton L. Lee (Archives of Environmental Contamination and Toxicology, 1986)